Bacteriocins from the rhizosphere microbiome – from an agriculture perspective - Subramanian, Sowmyalakshmi; Smith, Donald L. (Frontiers in Plant Science, 2015)
Bacteria produce and excrete a versatile and dynamic suit of compounds to defend against microbial competitors and mediate local population dynamics. These include a wide range of broad-spectrum non-ribosomally synthesized antibiotics, lytic enzymes, metabolic by-products, proteinaceous exotoxins and ribosomally produced antimicrobial peptides (bacteriocins). Most bacteria produce at least one bacteriocin. Bacteriocins are of interest in the food industry as natural preservatives and in the probiotics industry, leading to extensive studies on lactic acid bacteria (colicin produced by Escherichia coli is a model bacteriocin). Recent studies have projected use of bacteriocins in veterinary medicine and in agriculture, as a biostimulants of plant growth and development and as biocontrol agents. For example, bacteriocins such as Cerein 8A, Bac-GM17, putidacin, Bac 14B, amylocyclicin have been studied for their mechanisms of anti-microbial activity. Bac IH7 promotes tomato and musk melon plant growth. Thuricin 17 (Th17) is the only bacteriocin studied extensively for plant growth promotion and at the molecular level. Th17 functions as a bacterial signal compound, promoting plant growth in legumes and non-legumes. In Arabidopsis thaliana and Glycine max Th17 increased phytohormones IAA and SA at 24 h post treatment. At the proteome level Th17 treatment of 3-week-old A. thaliana rosettes led to > 2-fold changes in activation of the carbon and energy metabolism pathway proteins, 24 h post treatment. At 250 mM NaCl stress, the control plants under osmotic-shock shut down most of carbon-metabolism and activated energy-metabolism and antioxidant pathways. Th17 treated plants, at 250 mM NaCl, retained meaningful levels of the light harvesting complex, photosystem I and II proteins and energy and antioxidant pathways were activated, so that rosettes could better withstand the salt stress. In Glycine max, Th17 helped seeds germinate in the presence of NaCl stress, and was most effective at 100 mM NaCl. The 48 h post germination proteome suggested efficient and speedier partitioning of storage proteins, activation of carbon, nitrogen and energy metabolisms in Th17 treated seeds both under optimal and 100 mM NaCl. This review focuses on the bacteriocins produced by plant-rhizosphere colonizers and plant-pathogenic bacteria, that might have uses in agriculture, veterinary and human medicine.